O Uso das ferramentas TDIC no processo de ensino: um estudo aplicado no IFPA Campus Castanhal - COSTA JUNIOR, Antônio Carlos Dantas da (Universidade Federal do Pará, 2025)
Digital Information and Communication Technologies are innovative tools that can help in the development of education. However, its effective implementation requires understanding and qualification of its use, in addition to investment and expansion of access to equipment and internet. Its emergency use during the pandemic can serve as an element of analysis for its implementation in everyday education. The study aims to investigate the use of Digital Information and Communication Technologies at the Instituto Federal do Pará - Campus Castanhal as a tool for remote teaching. The research, in terms of methodology, was exploratory-descriptive. In relation to the procedures, it was configured as a bibliographic and documentary review, also involving field research. Regarding the approach and analysis, quantitative and qualitative methods were combined (mixed method). The field research was carried out at the Federal Institute - Castanhal campus, state of Pará. The qualitative and quantitative responses provided the main categories of analysis for this study, highlighting several impacts arising from the transition from in-person to remote teaching during the pandemic. The study identified barriers, limits and potentialities in pedagogical and management practice, highlighting rigidity in training and practices in relation to the dynamic nature of the world. It highlighted the importance of training education professionals for emergencies, including health, climate, war and socioeconomic crises. The socioeconomic inequality of students, especially in remote communities, is a barrier magnified by the lack of access to technologies. Digital Information and Communication Technologies can be allies, but they must be tools and not protagonists of human relationships that strengthen educational processes. The study highlighted that technologies, when properly used, are valuable aids for education, to mitigate socioeconomic and territorial inequalities, especially in the Amazon region, and to effectively foster democratic education. Public policies need to include access to technology, as well as changes in the training and training of teachers and managers are essential, and are also responsibilities of governance and public investments.